Anti-influenza activity of Blumea Balsamifera (L.) DC. Extract: In vitro and in vivo evaluation against multiple influenza virus strains - Zhen Chen; Ming Cai; Li Chai; Xia Li; Rongcheng Wen; Jinyan Jia; Huang Li; Fei Yu (Virus Research, 2025)
Influenza virus epidemics occur annually, posing significant public health challenges. Although anti-influenza drugs are available, newly emerged viral strains frequently develop resistance, necessitating the discovery of new antiviral reagents. This study aims to evaluate the anti-influenza virus activity of Blumea Balsamifera (L.) DC. Extract (BBE) in both in vitro and in vivo settings. The antiviral activity of BBE was assessed using the CellTiter-Glo assay and the cytopathic effect (CPE) assay in Madin-Darby canine kidney (MDCK) cells, targeting influenza virus strains H1N1, H3N2, and four influenza B viruses. Specifically, BBE demonstrated significant inhibition of MDCK cell lesions caused by the A subtypes A/WSN/33 (H1N1) and A/Hong Kong/4801/2014 (H3N2), as well as the B subtypes B/Darwin/58/2019 (Yamagata), B/Phuket/3073/2013 (Yamagata), B/Sichuan Gaoxin/531/2018 (Victoria), and B/Brisbane/60/2008 (Victoria). The extract showed inhibitory concentration (IC50) values of 8.71, 11.38, 10.14, 4.66, 3.17, and 4.29 μg/mL, respectively. Time-of-drug-addition assay results indicated that BBE inhibits the early stages of influenza virus replication. Additionally, in vivo studies in murine models further confirmed the protective effects of BBE, where it reduced viral-induced weight loss, delayed mortality, and mitigated lung tissue damage. These findings suggest that Blumea Balsamifera (L.) DC. extract holds promise as a potential reagent against influenza viruses and warrants further investigation.